2017
DOI: 10.1002/fam.2418
|View full text |Cite
|
Sign up to set email alerts
|

Mass loss and flammability of insulation materials used in sandwich panels during the pre‐flashover phase of fire

Abstract: Summary Nowadays, buildings contain more and more synthetic insulation materials in order to meet the increasing energy‐performance demands. These synthetic insulation materials have a different response to fire. In this study, the mass loss and flammability limits of different sandwich panels and their cores (polyurethane (PUR), polyisocyanurate (PIR) and stone wool) are studied separately by using a specially designed furnace. Expanded polystyrene and extruded polystyrene are tested on their cores only. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Owing to high softening temperature, excellent foaming property, and mechanical performance, polystyrene (PS) has been used in electric and electronic devices, packaging and expandable foams, etc . As one of 5 general engineering plastics, PS also exhibited fire hazards especially in case of high‐demanding circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to high softening temperature, excellent foaming property, and mechanical performance, polystyrene (PS) has been used in electric and electronic devices, packaging and expandable foams, etc . As one of 5 general engineering plastics, PS also exhibited fire hazards especially in case of high‐demanding circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…A small amount of char experienced a higher amount of mass loss as possess higher flammability (Mouritz and Gibson, 2006). Giunta d'Albani et al (2017) used a heated furnace for analysing the mass loss of different polymers such as PU, PIR, EPS and XPS, which are commonly used in cladding panels. Mass loss of most polymers was observed at the range of temperature between 250°C and 400°C.…”
Section: Flame Behaviour Of Lightweight Composite Cladding Materialsmentioning
confidence: 99%
“…At 250°C only 2% mass loss is observed, but it increased sharply at 400°C. The mass loss of polymers such as PIR, PU and PS polymers at 400°C is 28%, 44% and 87%, respectively (Giunta d'Albani et al , 2017). Jiao et al (2012) observed a multi-stage thermal degradation of XPS.…”
Section: Flame Behaviour Of Lightweight Composite Cladding Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of different proportions of mineral wool and polyurethane foam on the results of the fourpoint bending tests were investigated. It should be clearly noted that a number of research projects devoted to panels with mineral wool core dealt with issues of fire resistance [14].…”
Section: Introductionmentioning
confidence: 99%